Study of types of defects in wood chipboard production; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Vasendina E. A. Elena Aleksandrovna; Plotnikova I. V. Inna Vasilievna; Redko L. A. Lyudmila Anatolevna; Zyablova N. N. Natalia Nikolaevna (2015, 2015)
Title screen